Materiais didáticos em cursos do PROEJA: concepção e utilização pelos professores do Campus São Luís/Maracanã - IFMA - NASCIMENTO, Michelle de Cássia Barros (2017)
The present Master Thesis is part of the Research Group "School, Curriculum, Training and Teaching Work" of the Post-Graduation Program in Education of the Federal University of Maranhão. We analyze the relationship between the teaching materials adopted by teachers in the teaching and learning process of the technical courses of the National Integration Program of Vocational Education with Basic Education in the modality of Youth and Adults Education (PROEJA) and the guiding principles of this program. The methodological approach that guides this study is qualitative, because it allows an interpretative analysis, involving the multiple determinations of the investigated phenomenon and to allow the understanding of the phenomena from the perception of the investigated subjects, supported by Richardson et al (2007) and Lessard-Hérbert et al (1990). The techniques and instruments of data collection applied were the semi-structured interview for teachers and pedagogical coordinator and the questionnaire for the students. The sample of this research was composed of ten teachers, one coordinator and ten percent of the students, corresponding to eighteen students, enrolled in PROEJA technical courses at Campus São Luís/Maracanã - IFMA and the categories of analysis were: Teaching materials, PROEJA and Curriculum. The theoretical basis that support us regarding curriculum and teaching materials were the works of Barbosa (2005), Bittencourt (1993), Choppin (2004), Mello (2010), Munakata (2012), Rangel (2006), Ramos (2001; 2005), Silva (2005) and Young (2013) and in the field of EJA, Arroyo (2001; 2011), Beisiegel (2004), Brasil (2000; 2007), Fávero (2008), Freire (1987, 2011), Haddad (2000; 2014) Jardilino and Araújo (2014) and Paiva (1973), among other scholars of these topics, in addition to analyzing documents such as the Law of Guidelines and Bases 9394/96, Curriculum Guidelines for Basic Education, Curriculum Guidelines for Youth and Adult Education, the PROEJA Basis Document, the Pedagogical Political Project of Campus São Luís/Maracanã, the Course Plans, Resolutions and Policy adopted internally at IFMA. The research results allowed us to conclude that the teaching material is present in the teachers’ pedagogical practice of Campus São Luís/Maracanã and they are essential elements for a good performance of teaching. Both students and teachers emphasized the importance of these elements for the learning process. Revealing that the lack of continuous training has prevented or at least limited the performance of teachers who showed an interest in developing a work focused on the real needs of the subjects served by PROEJA. The relevant place that teaching material still have in teaching only reinforces the need to broaden the research on this subject, especially in the EJA.